Pengaruh Work Family Conflict dan Ketidakjelasan Peran Terhadap Stres Kerja Pada PT. Honda Makassar Indah Cabang Utama - Dharmawaty Djaharuddin; Nur Syamsu; Mokhtar, Susiana (Insan Cita Bongaya Research Journal, 2024)
This research aims to determine the influence of work family conflict and role ambiguity on work stress at PT.Hond Makassar Indah Main Branch. The population in this study was 150 employees. The sampling technique used was the Slovin Formula technique, so the entire population at the Kudam XIV/Hasanuddin Office was sampled, namely 60 respondents. The analytical method used is multiple linear regression analysis, t test, and dominant test with the help of SPSS version 27 software. The research results show that (1) Work Family Conflict has a positive and significant effect on Job Stress. (2) Role Ambiguity has a positive and significant effect on Job Stress. (3) Work Family Conflict is the most dominant variable in this research